A NOVEL ROUTE DESIGN METHODOLOGY BASED ON MINIMIZING LEVEL DIFFERENCES BETWEEN GRADE AND GROUND LINE - Tunalioglu, Nursu; Soycan, Metin (ASSOC SURVEYORS SLOVENIA, 2014)
The route design method developed here is proposed to define the least-elevation differences between the grade and ground line. The method is based on setting the grade line as closely as possible to the natural ground level. The objective function of the proposed model is thus described with the topographic features of the area. The longitudinal gradient is taken as a condition and the minimization of the elevation differences between grade and ground line performs the objective function. The decision variables of the method are the horizontal coordinates within the boundaries of the study region. Initially, the proposed grade profile of the route is computed and determined by the three-dimensional coordinates of given start and endpoints. Then, the cross section stations are taken at regular intervals along the grade line. The adequate horizontal coordinates of the cross section stations are obtained by intersecting the grade lines and contour levels. The reliability of the model relies on standard deviation of elevation differences along the profile. The results show that the model may be used as a guide for route selection facilities based on topographic features of the area of interest. The methodology is implemented using a graphical interface and function developed in Matlab programming language.
Keywords: route design; topography; elevation model; optimization; grade condition; Matlab; GEOGRAPHIC INFORMATION-SYSTEMS; HIGHWAY ALIGNMENT; GENETIC ALGORITHMS; EARTHWORK COST; ROADWAY GRADES; MODEL; SELECTION; Geography